Cytotoxicity Assay of Chitosan-Collagen Wound Dressing using Brine Shrimp Lethality Test Methods - Ary Andini; Ersalina Nidianti; Endah Prayekti (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Wound dressing has a function to protect the wound area from external exposure and provide a moist state around the wound area for accelerating wound healing process. Collagen and chitosan are known as appropriate biomaterials to synthesise of wound dressing because they have anti-bacterial, anti-fungal, biodegradable and biocompatible properties. One of biocompatibility assay for a material is cytotoxicity assay using Brine Shrimp Lethality Test (BSLT) that could be applied before in Vivo assay. The aim of the research was to know the cytotoxicity level of collagen-chitosan wound dressing with variance of concentration such as K0 as control used pure chitosan, K1 used collagen 25% and chitosan 75%, K2 used collagen 50% and chitosan 50%, K3 used collagen 75% and Chitosan 25%. Skin and scales of Gabus fish (Channa striata) were extracted using 2% HCl solvent to obtain collagen and chitosan powder dissolved in 1% acetic acid. Furthermore, wound dressing is made by a combination of collagen-chitosan concentration according to each group (K0, K1, K2 and K3. Citotoxicity assay used Brine Shrimp Level Test (BSLT) method with concentration each sample group were 10, 50, 100, 250, 500, 750 and 1000 ppm. The results showed that each wound dressing group such as K0, K1, K2 and K3 had LC50> 1000ppm that indicated wound dressing was non-toxic.